2017
DOI: 10.1002/adfm.201605588
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing Design Principles toward Efficient, Long‐Term Stable Green Light‐Emitting Electrochemical Cells

Abstract: 1 of 8) 1605588be based on non-air sensitive materials allowing for cheap ambient device processing techniques such as spin coating, roll-to-roll, and slot die coating, (iii) even the electrodes can be made out of stable (even noble) metals as the ionic nature of emissive layer omits the need for electrodes made out of metals with low work functions, and (iv) that it is fairly easy to produce large emitting areas. [1][2][3][4][5][6][7][8][9][10] Altogether this makes LECs a very promising low-cost, large area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 42 publications
3
34
1
Order By: Relevance
“…We have in this study focused on the emission from a Super Yellow-based LEC, but the results should be applicable also for LECs based on other emitters. The emission from an optical microcavity is the product of the intrinsic emission spectrum of the emitter and the cavity gain, which implies that broad emitters, such as conjugated polymers 4 , 33 , 45 , 47 , 48 and ionic transition metal complexes 49 53 (the two most common emitter materials in LECs), can encompass multiple cavity modes depending on the active-layer thickness and the viewing angle; this feature is clearly displayed in Fig. 2 54 , 55 .…”
Section: Resultsmentioning
confidence: 99%
“…We have in this study focused on the emission from a Super Yellow-based LEC, but the results should be applicable also for LECs based on other emitters. The emission from an optical microcavity is the product of the intrinsic emission spectrum of the emitter and the cavity gain, which implies that broad emitters, such as conjugated polymers 4 , 33 , 45 , 47 , 48 and ionic transition metal complexes 49 53 (the two most common emitter materials in LECs), can encompass multiple cavity modes depending on the active-layer thickness and the viewing angle; this feature is clearly displayed in Fig. 2 54 , 55 .…”
Section: Resultsmentioning
confidence: 99%
“…We stress that the T ( LVB ) lifetime can be defined differently for a different material system and under different testing conditions. Some iTMC‐based LECs, for example, exhibit a highly stable average driving voltage under pulsed current operation . The purpose of introducing this new figure‐of‐merit is to quantitatively account for the contribution of voltage drift and black spots to the operational stability of LECs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on saturated red LECs, based on iTMCs, have been reported. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However,m ost of these studies involve LECs that exhibit low or moderate device efficiencies (externalq uantum efficiency (EQE) < 3.3%); saturated red LECs that are moree fficienta re highlyd esired. In iridium iTMCs, the highest occupied molecular orbital (HOMO) is typicallyd istributed on the C^N ligands and metals, whereas the lowest unoccupiedm olecular orbital (LUMO) is locatedo nt he N^N ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Saturated red‐light sources, which exhibit emission peak wavelengths longer than approximately 640 nm, are essential for full‐color displays because they can generate a large color gamut. Several studies on saturated red LECs, based on iTMCs, have been reported . However, most of these studies involve LECs that exhibit low or moderate device efficiencies (external quantum efficiency (EQE) <3.3 %); saturated red LECs that are more efficient are highly desired.…”
Section: Introductionmentioning
confidence: 99%